Has Lexicography Arrived as an Academic Discipline? Reviewing Progress in Dictionary Research during the Last Three Decades - Hartmann, Reinhard (Nordiske Studier i Leksikografi, 2010)
The current position of lexicography is discussed by attempting tentative answers to six sets of questions: 1) What are some of the most important events since 1977, and how have they contributed to raising the status of lexicography? 2) Who are the leaders of dictionary research, especially as founders of dictionary research centres? 3) What are the chief component parts or perspectives for the definition of dictionary research? 4) What are the criteria for disciplinary status (and most appropriate methods of research)? 5) What are the remaining deficiencies in dictionary research? and 6) What are the implications of all of this for the future? The main points are supported by tables exemplifying developments that I have found to be of particular interest.